Screening Genders : The American Science Fiction Film - Luhr, William; Gabbard, Krin (Book collections on Project MUSE., 2008)
Gender roles have been tested, challenged, and redefined everywhere during the past 30 years, but perhaps nowhere more dramatically than in film. This book is an introduction to the evolving representations of masculinity, femininity, and places once thought to be 'in between'